Viewpoints of the Occupational Therapist Assistant–Physiotherapist Assistant Role on Inter-Professional Teams: A Mixed-Methods Study. - Penner, Jacklyn D.; Snively, Amanda; Packham, Tara L.; Henderson, Jennifer; Principi, Elaine; Malstrom, Brooke (Physiotherapy Canada)
Purpose: Occupational therapist assistants and physiotherapist assistants work on inter-professional teams in both institutional and community settings to facilitate patients' rehabilitation and recovery. Examination of how the assistant role is viewed by assistants and other inter-professional team members is needed to inform how to support and sustain development of the role and associated practice relationships. Method: In this explanatory sequential-design mixed-methods study, we first surveyed rehabilitation personnel, then held focus groups at a large urban health care organization. Statistical and thematic analysis was conducted to combine the findings from both data sources. Results: A total of 89 therapists and assistants completed surveys; 30 also contributed to four focus groups. Five themes were developed that expressed the perceptions of the assistant role on inter-professional teams: (1) left out of the loop, (2) living in the grey: negotiating and navigating the assistant role, (3) who's the boss? (4) things just don't fall into your lap: pursuing professional development, and (5) (not) just the assistant: the influence of norms and attitudes and external perspectives. Conclusions: The findings describe perceptions and institutional norms of the assistant practice role. They can inform discussions on regulation and accreditation as well as professional and continuing education, and they can promote reflection on team dynamics and supervisory practices.